PENGGUNAAN APLIKASI SEO UNTUK OPTIMALISASI PROMOSI PARIWISATA BAGI PEMUDA DI BANDAR LAMPUNG - Simon Sumanjoyo Hutagalung; Robi Rakhmadi (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
Regional tourism promotion can be done with SEO, but in the context of regional tourism promotion in Bandar Lampung City, it is known that the constraints are on the skills and knowledge of youth groups to apply SEO. This activity aims to (1). Increase the content of knowledge possessed by youth groups in supporting regional tourism promotion, and (2). Improve the skills of youth groups in applying SEO for the benefit of regional tourism promotion. This activity is carried out with a training method that presents material related to knowledge about SEO applications and strengthening skills in using SEO applications. The target audience involved 15 young people who actively use social media and digital tourism campaigns. Based on the qualitative evaluation conducted, participants of regional tourism promotion activities were satisfied and felt that the activities were in accordance with their needs. Almost all participants actively participated in the discussion, so it can be concluded that the activity has achieved the expected goals and objectives.